2020
DOI: 10.5195/jmla.2020.983
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of adverse drug reaction formatting in drug information databases

Abstract: Objective: The research evaluated the differences in formatting of adverse drug reaction (ADR) information in drug monographs in commonly used drug information (DI) databases.Methods: A cross-sectional analysis of formatting of ADR information for twenty commonly prescribed oral medications in seven commonly used DI databases was performed. Databases were assessed for presentation of ADR information, including presence of placebo comparisons, severity of ADR, onset of ADR, formatting of ADRs in percentile (qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The first step is a computational and semantic comparison of case history to the medications the patient is taking. This is powered by DrugBank [ 25 ], Epocrates [ 26 ], and Lexicomp [ 27 ] to tally the subset of symptoms that are present and known to occur as side effects of the medications the patient is taking. At a clinical informatics level, cough with fever might be connected/mapped to curated ontologies such as SNOMED (Systematized Nomenclature of Medicine [ 28 ]) about SARS-CoV-2, or pneumonia in a weighted fashion, by subject matter experts who then have the capability to markedly enhance this highly navigable information.…”
Section: Resultsmentioning
confidence: 99%
“…The first step is a computational and semantic comparison of case history to the medications the patient is taking. This is powered by DrugBank [ 25 ], Epocrates [ 26 ], and Lexicomp [ 27 ] to tally the subset of symptoms that are present and known to occur as side effects of the medications the patient is taking. At a clinical informatics level, cough with fever might be connected/mapped to curated ontologies such as SNOMED (Systematized Nomenclature of Medicine [ 28 ]) about SARS-CoV-2, or pneumonia in a weighted fashion, by subject matter experts who then have the capability to markedly enhance this highly navigable information.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to a previous study of DI desktop applications, we identified variability across DI mobile applications in a variety of formatting parameters that are known to influence clinical decision-making [ 24 ]. Mobile applications varied substantially with regard to the presence of comparative placebo information, ADR severity information, referencing, organization by organ system, and both quantitative and qualitative formatting.…”
Section: Discussionmentioning
confidence: 97%
“…This study has a number of limitations. First of all, this project, similar to the previous analysis of DI databases, was limited to an assessment of twenty medications [ 24 ]. However, by evaluating the most widely prescribed medications in the United States, including drugs that were approved over disparate periods of time (and thus under varying degrees of regulatory approval by the Food and Drug Administration), we believe the information drawn from the monographs within the analyzed mobile applications is likely a good representation of ADR formatting more generally [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations